Sex-specific outcomes after transcatheter or surgical treatment of aortic valve stenosis: the DEDICATE-DZHK6 trial - Bleiziffer, Sabine; Leuschner, Florian; Rudolph, Tanja; Vonthein, Reinhard; Meyer, Anna L.; Häusler, Karl Georg; Hofmann, Ulrich; Erasmi, Armin; Hagendorff, Andreas; Kim, Won-Keun; Baumgartner, Helmut; Borger, Michael A.; et al. (European heart journal, 2025)
Aortic stenosis may be managed differently in women and men, but evidence remains limited. Sex-specific characteristics and outcomes of low- to intermediate-risk patients assigned to transcatheter aortic valve implantation (TAVI) or surgical aortic valve replacement (SAVR) from the DEDICATE-DZHK6 trial are described.The DEDICATE-DZHK6 trial demonstrated non-inferiority for the primary outcome of all-cause death or stroke at 1 year. Sex-specific effects were evaluated in this predefined descriptive subgroup analysis.A total of 1394 patients (43.3% women) were included. Women were older (women: 74.8 ± 4.6 years vs men: 74.2 ± 4.2 years, P = .020) and at higher operative risk [median Society of Thoracic Surgeons risk score 2.1% (1.5-2.7) vs 1.5% (1.0-2.2), P < .001]. All-cause death or stroke at 1 year was 5.2% in the TAVI vs 11.5% in the SAVR group [hazard ratio (HR) 0.46; 95% confidence interval (CI) 0.25-0.82] in women and 5.4% vs 9.0% (HR 0.61; 95% CI 0.35-1.03) in men. At 1 year after TAVI vs SAVR, all-cause death occurred in 2.6% vs 6.7% (HR 0.41; 95% CI 0.17-0.90) in women and 2.6% vs 5.9% (HR 0.44; 95% CI 0.20-0.88) in men. Stroke occurred in 2.6% vs 6.2% (HR 0.43; 95% CI 0.18-0.93) in women and 3.1% vs 3.6% (HR 0.89; 95% CI 0.41-1.90) in men.Among patients with severe aortic stenosis at low to intermediate risk, TAVI was non-inferior to SAVR for the primary outcome in women and men with lower event rates in patients assigned to TAVI. Women were at particular risk for early complications irrespective of the assigned treatment and at increased stroke risk after SAVR.
Gesehen am 16.10.2025